Analysis of Water Pricing Policy Effects in a Mediterranean Basin Through a Hydroeconomic Model - Martínez-Dalmau, Javier; Gutiérrez-Martín, Carlos; Expósito, Alfonso; Berbel, Julio (Water resources management, 2023)
This paper explores the impacts of water pricing as a demand management policy, at a regional level (or basin-sector). To this aim, a hydro-economic model for the Guadalquivir River basin (southern Spain) is proposed here. This basin constitutes a perfect example of a Mediterranean basin subject to frequent and long drought periods, where challenges related to water scarcity are increasing, leading to social conflicts among water users. Moreover, this basin is characterised by a closure state meaning that all available water resources are already allocated among users. In this context, water pricing policy may act as an effective tool to reduce water demand by encouraging changes of behaviour in water users. In particular, those who perform irrigation practices in the agricultural sector. This paper focuses on the irrigation sector since it is the main water user in the basin (87%). Additionally, alternative water-availability scenarios have been used to test the effect of water pricing under drought conditions. The hydro-economic model presented here has been sectorized into four basin sectors with common characteristics (hydro and economic). This enables the analysis of alternative price scenarios in the agricultural sector, in terms of water used, crop patterns and gross margin. Results show that water pricing policy should consider the regional characteristics at the basin-sector scale to gain effectiveness and equity at the river basin scale. Moreover, it has been found that both water availability and the crop pattern at the basin-sector scale have an effect on the reduction of water used (and therefore in gross margin.